5-ASA Suppositories in Hemorrhoidal Disease - P Gionchetti; M Campieri; A Belluzzi; C Brignola; M Miglioli; L Barbara (Canadian Journal of Gastroenterology)
Forty patients with active hemorrhoidal disease were entered into this double-blind trial, 20 of whom were randomized to treatment with 5-aminosalicylic acid (5-ASA) (500 mg) suppositories. Clinical and sigmoidoscopic assessment was carried out before the start of the trial and after two weeks of treatment. At the end of the study, 5-ASA suppositories showed results superior to those of placebo for all parameters evaluated (P<0.01). There were no adverse events reported related to the use of suppositories. 5-ASA suppositories are a valid therapeutic approach for hemorrhoidal disease as it reduces the intensity of all symptoms and significantly decreases congestion of the hemorrhoidal plexus.